Optimalisasi Fragmentasi dengan Metode KUZ-RAM pada Penambangan Batu Andesit - Laura Puspita Sari; Faturrahmat Widodo (PROMINE, 2021)
The main activities at a mining site consist of stripping the overburden, unloading by blasting and surface mining, loading and transporting from the mining location to the crushing location. Blasting is an activity in mining that is carried out with the aim of dismantling the rock from its source rock into a predetermined size to facilitate further processes such as loading and crushing and a set production target. The less boulder, the better the resulting fragmentation because it will reduce the production costs for crushing the boulder to be smaller. This research focuses on blasting geometry planning as a parameter that is considered important in changing the size of the blasting rock fragmentation. The andesite blasting activity at the Batujajar 1 mine still found a fairly large percentage of rock blocks. Based on field observations, rock blocks resulting from blasting activities in the Batujajar 1 quarry are as follows: burden (B) 2.4 m, space (S) 3.1 m, stemming (T) 1.8 m, subdrilling (J ) 0 m, height (L) 6 m, into the blast hole (H) 6 m, column of explosives (Pc) 4.2 m, explosive material as much as 11.07 kg / hole. The drilling pattern applied is a staggered pattern and corner cut blasting pattern which is blasted in a row for each line with a delay time of 25 ms. The proposed geometry is calculated by calculating RL Ash 1963. With the theoretically proposed blasting geometry the results of rock chunks measuring> 80 cm according to RL Ash 1963 are 0.18%, then selected with the 1963 RL Ash theory, the results of rock fragmentation sizes are> 80 cm is 0.18%, this amount is better than the actual rock fragmentation which is still 9.11%, with the reduced number of boulders it is expected that production activities will run better.